Zur Faltenwespenfauna der Insel Hiddensee. Ein Beitrag zur Fauna von Naturschutzgebieten der DDR (Hymenoptera: Vespoidea). - Oehlke, Joachim (Contributions to Entomology = Beiträge zur Entomologie, 1979)
The study of the Hymenoptera of Hiddensee is continued and 13 species of Vespidae are established for this island. It is remarkable that the genus Polistes and Eumenidae are absent.